Curable thermally conductive composition

JP2025505179APending Publication Date: 2025-02-21DOW SILICONES CORP
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2024546220
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2022-02-07
Publication Date
2025-02-21

Smart Images

  • Figure 2025505179000001
    Figure 2025505179000001
  • Figure 2025505179000002
    Figure 2025505179000002
  • Figure 2025505179000003
    Figure 2025505179000003
Patent Text Reader

Abstract

The curable thermally conductive composition comprises: (A) an alkenyl-functional polyorganosiloxane having a viscosity in the range of 25 to 2000 millipascals*seconds; (B) a silyl-hydride-functional polysiloxane crosslinker; and (C) (c1) 30 to less than 55 weight percent aluminum particles having a D50 of 60 micrometers or more; (c2) 20 to 40 weight percent thermally conductive filler having a D50 of 1 to 10 micrometers; (c3) 8 to 20 weight percent aluminum particles having a D50 of 0.1 to less than 1 micrometers. and (c4) optionally, zero to 20 weight percent of a thermally conductive filler other than (c1) having a D50 of 20 to 80 micrometers; and (D) 0.1 to 2.5 weight percent of a filler treating agent comprising a trialkoxysilyl diorganopolysiloxane, and optionally an alkyltrialkoxysilane, the weight percentages being based on the weight of the curable thermally conductive composition.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a curable thermally conductive composition containing a thermally conductive filler comprising aluminum particles having a D50 particle size in the range of 60 to 150 micrometers.

[0002] Introduction The trend of miniaturization and power of electronic devices in industry has increased the demand for thermally conductive compositions that are useful for dissipating heat generated by such devices. For example, the telecommunications industry is undergoing a generational shift to 5G networks, which requires small highly integrated electric devices and doubles the power requirements (from 600 watts to 1200 watts). If the heat generated by the high power in small devices is not efficiently dissipated, the devices will be damaged. Thermally conductive interface materials are often used in electronic devices to thermally couple heat-generating components with heat-dissipating components.

[0003] The challenge of thermally conductive interface materials is to provide a combination of both high thermal conductivity properties and being easily extrudable to allow for precise application of the thermally conductive material onto small components. In particular, it is desirable to provide a thermally conductive interface material that has an extrusion rate of at least 40 grams per minute as measured using the Extrusion Rate Test defined herein below, and cures into a material that has a thermal conductivity of at least 10 watts per meter per kelvin as measured using a hot disk according to ISO 22007-2. Thermal conductivity can be increased by increasing the amount of thermally conductive filler, but this also reduces the extrusion rate of the composition, which may further reduce the composition to a powdery paste. Thus, meeting these two performance parameters is particularly difficult.

[0004] There remains a need to identify thermally conductive compositions that can simultaneously achieve the above extrusion speeds and thermal conductivity properties. Summary of the Invention

[0005] The present invention provides a thermally conductive interface material having an extrusion rate of 40 grams per minute (g / min) or greater as measured using the Extrusion Rate Test defined herein below, and curing to a material having a thermal conductivity of at least 10 Watts per meter per Kelvin (W / m*K) using a hot disk according to ISO 22007-2. Surprisingly, it has been determined that such a composition can be prepared from a curable polysiloxane composition (also "curable thermally conductive composition") containing 94-97 weight-percent (wt-%) of a thermally conductive filler including less than 30-55 weight-percent (wt-%) aluminum particles having a D50 particle size in the range of 60-150 micrometers (μm), where wt-% is based on the weight of the curable polysiloxane composition.

[0006] In a first aspect, the present invention provides a curable thermally conductive composition comprising: (A) 1.0 to 4.0 weight percent of an alkenyl-functional polyorganosiloxane having a viscosity in the range of 25 to 2000 millipascals*seconds as determined by ASTM D445-21 using a glass capillary Cannon-Fenske viscometer at 25 degrees Celsius, the alkenyl-functional polyorganosiloxane having an average chemical structure (I) [ka] In the formula, R a is, independently at each occurrence, an alkyl group having 1 to 6 carbon atoms; R' is, independently at each occurrence, an alkenyl group; subscript a > 0; subscript b > 0; subscript c is zero or 1; subscript d is zero or 1; (a + b) is 20 to 350; and (a + c + d) > 2; (B) a silyl-hydride functional polysiloxane crosslinker containing at least two silyl-hydride groups per molecule and present in a concentration providing a molar ratio of silicon-bonded hydrogen atoms to alkenyl groups of the composition of from 0.4 to 1.5; (C) 94 to 97 weight percent of a thermally conductive filler, (c1) 30% to less than 55% by weight of aluminum particles having a D50 in the range of 60 to 150 micrometers; (c2) 20 to 40 weight percent of a thermally conductive filler having a D50 in the range of 1 to 10 micrometers; (c3) 8 to 20 weight percent of a thermally conductive filler having a D50 in the range of 0.1 to less than 1 micrometer; and (c4) optionally comprising zero to 20 weight percent of a thermally conductive filler other than (c1) having a D50 in the range of 20 to 80 micrometers; (D) 0.1 to 2.5 weight percent of a filler treating agent comprising a trialkoxysilyl diorganopolysiloxane, and optionally an alkyltrialkoxysilane; The weight percentages are based on the weight of the curable thermally conductive composition.

[0007] In a second aspect, the invention is a process for using the curable thermally conductive composition of the first aspect, the process comprising applying the curable thermally conductive composition between and in contact with two components, and then curing the curable composition while in place between the components.

[0008] In a third aspect, the invention is an article comprising the curable thermally conductive composition of the first aspect between and in contact with two components of the article, the curable thermally conductive composition being either in a cured or uncured form. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0009] Test methods refer to the test method most recent as of the priority date of this document unless a date is given with the test method number. Reference to a test method includes both a reference to the testing society and the test method number. In this specification, the following test method abbreviations and identifiers apply, ASTM refers to ASTM International methods and ISO refers to International Organization for Standardization standards.

[0010] Products identified by trade names refer to compositions available under those trade names as of the priority date of this document.

[0011] "And / or" means "and, or alternatively." All ranges are inclusive of the endpoints unless otherwise indicated.

[0012] A particle having a "spherical" shape refers to a particle having an aspect ratio of 1.0 + / - 0.2. Scanning electron microscope (SEM) imaging is used to determine the aspect ratio of a particle by taking the average ratio of the longest dimension (major axis) to the shortest dimension (minor axis) of at least 10 particles.

[0013] "Irregular" shaped particles have an aspect ratio other than 1.0 + / - 0.2 and have at least three sides evident by SEM imaging (distinguishing particles from "plates" which have two sides).

[0014] Particle size (used interchangeably with "average particle size" and "D50") of the thermally conductive fillers refers to the volume weighted median (D50) of the particle size distribution using a Mastersizer™ (trademark of Malvern Instruments Limited) 3000 laser diffraction particle size analyzer from Malvern Instruments.

[0015] Viscosity is determined according to ASTM D445-21 using a glass capillary Cannon-Fenske viscometer at 25 degrees Celsius (° C.) unless otherwise specified.

[0016] The curable thermally conductive compositions of the present invention are capable of undergoing a crosslinking reaction ("cure"), in which the crosslinking reaction is a hydrosilylation reaction between an alkenyl-functional polyorganosiloxane component and a silyl-hydride (SiH)-functional polysiloxane crosslinker.

[0017] Alkenyl-functional polyorganosiloxanes useful in the present invention have two or more alkenyl groups per molecule. By "alkenyl" is meant a branched or unbranched monovalent hydrocarbon group having one or more carbon-carbon double bonds. The alkenyl groups can be terminal, pendant, or a combination of both terminal and pendant. A "terminal" group is on a terminal siloxane group of the molecule. A "terminal" siloxane group is bonded to only one other siloxane group. A "pendant" group is on an internal siloxane group of the molecule (a siloxane group bonded to at least two other siloxane groups). A "siloxane group" is a group containing SiO that is bonded to another Si through the oxygen of the SiO. Desirably, the alkenyl-functional polydiorganosiloxane has an average of one or more terminal alkenyl groups per molecule. The alkenyl-functional polyorganosiloxane has a viscosity in the range of 25 to 2000 millipascals*seconds (mPa*s). The alkenyl-functional polyorganosiloxane may be a combination of two or more alkenyl-functional polyorganosiloxanes, which may differ in one or more properties selected from molecular weight, structure, siloxane units, and sequence. When the alkenyl-functional polyorganosiloxane is a combination of two or more alkenyl-functional polyorganosiloxanes, the viscosity is the combined viscosity of the alkenyl-functional polyorganosiloxanes. The viscosity of the alkenyl-functional polyorganosiloxane is measured according to ASTM A1234. 25 mPa*s or more, when measured by using a glass capillary Cannon-Fenske type viscometer at 25 degrees Celsius (℃) in accordance with D445-21, including 30 mPa*s or more, 40 mPa*s or more, 50 mPa*s or more, 60 mPa*s or more, 70 mPa*s or more, 75 mPa*s or more, 78 mPa*s or more, 80 mPa*s or more, 100 mPa*s or more, 125 mPa*s or more, 1 It can be 50 mPa*s or more, 175 mPa*s or more, or even 200 mPa*s or more, and at the same time 2000 mPa*s or less, 1500 mPa*s or less, 1000 mPa*s or less, 500 mPa*s or less, 400 mPa*s or less, 300 mPa*s or less, 200 mPa*s or less, 150 mPa*s or less, 100 mPa*s or less, 90 mPa*s or less, or even 80 mPa*s.

[0018] The alkenyl-functional polyorganosiloxanes useful in the present invention may have the following average chemical structure (I): [ka] In the formula, R a is, independently at each occurrence, an alkyl group having 1 to 6 carbon atoms; R' is, independently at each occurrence, an alkenyl group; subscript a > 0; subscript b > 0; subscript c is zero or 1; subscript d is zero or 1; (a + c + d) > 2; and (a + b) is 20 to 350. a The group can have one or more carbons, two or more carbons, three or more carbons, four or more carbons, or even five or more carbons, and at the same time, six or fewer carbons, five or fewer carbons, four or fewer carbons, three or fewer carbons, or even two or fewer carbons. a can be CH3, CH2CH3, (CH2)2CH3, (CH2)3CH3, (CH2)4CH3, and (CH2)5CH3. Desirably, each R a is methyl. The alkenyl groups represented by R' typically have 2 to 8 carbon atoms, 2 to 6 carbon atoms, or 2 to 4 carbon atoms. Suitable alkenyl groups for R' are exemplified by alkenyl groups such as vinyl, allyl, butenyl, and hexenyl. Desirably, R' is vinyl. More desirably, subscript a is zero, subscript c is 1, subscript d is 1, and each R a is methyl.

[0019] The subscript a represents the (R'R a The subscript b is the average number of (R a2SiO) groups. Desirably, the amount (a+b) is 25 or more, 30 or more, 40 or more, 50 or more, 60 or more, 70 or more, 80 or more, 90 or more, 100 or more, 120 or more, 140 or more, 160 or more, 180 or more, 200 or more, 220 or more, 240 or more, 260 or more, 280 or more, 300 or more, 320 or more, or even 340 or more, and at the same time, typically, 350 or less, 340 or less, 320 or less, 300 or less, 280 or less, 260 or less, 240 or less, 240 or less, 220 or less, 200 or less, 180 or less, 160 or less, 140 or less, 120 or less, 100 or less, 80 or less, 60 or less, or even 40 or less.

[0020] Desirably, the amount (a+c+d) is 2 or greater, or even 3 or greater, and at the same time is typically 30 or less, and can be 20 or less, 10 or less, or even 3 or less.

[0021] Examples of suitable alkenyl-functional polyorganosiloxanes include i) vinyldimethylsiloxy-terminated polydimethylsiloxane, ii) dimethylvinylsiloxy-terminated poly(dimethylsiloxane / methylvinylsiloxane), iii) dimethylvinylsiloxy-terminated polymethylvinylsiloxane, iv) trimethylsiloxy-terminated poly(dimethylsiloxane / methylvinylsiloxane), v) trimethylsiloxy-terminated polymethylvinylsiloxane, vi) dimethylvinylsiloxy-terminated poly(dimethylsiloxane / methylvinylsiloxane), or mixtures thereof.

[0022] More desirably, the alkenyl-functional polyorganosiloxane comprises or consists of any combination of one or more vinyldimethylsiloxy-terminated polydimethylpolysiloxanes having the average chemical structure (II): [ka] wherein Vi represents vinyl and the subscript b is the average number of ((CH3)2SiO) groups per molecule and has a value of 20 or greater, and can be 25 or greater, 30 or greater, 40 or greater, 50 or greater, 60 or greater, 70 or greater, 80 or greater, 90 or greater, 100 or greater, 120 or greater, 140 or greater, 160 or greater, 180 or greater, 200 or greater, 220 or greater, 240 or greater, 260 or greater, 280 or greater, 300 or greater, 320 or greater, or even 340 or greater, and at the same time typically has a value of 350 or less, and can be 340 or less, 320 or less, 300 or less, 280 or less, 260 or less, 240 or less, 240 or less, 220 or less, 200 or less, 180 or less, 160 or less, 140 or less, 120 or less, 100 or less, 80 or less, 60 or less, or even 40 or less. For example, the alkyl-functional polyorganosiloxane can be a vinyldimethylsiloxy-terminated polydimethylsiloxane such as that available from Gelest under the product name SMS-V21, having a viscosity of 78 mPa*s and containing 1.25 weight percent (wt%) vinyl groups relative to the molecular weight.

[0023] The concentration of the alkyl-functional polyorganosiloxane can be 1.0 wt% or more, 1.5 wt% or more, 2.0 wt% or more, 2.4 wt% or more, 2.5 wt% or more, 2.6 wt% or more, 2.7 wt% or more, 2.8 wt% or more, 2.9 wt% or more, or even 3.0 wt% or more, and at the same time, generally, 4 wt% or less, 3.8 wt% or less, 3.5 wt% or less, 3.3 wt% or less, 3.0 wt% or less, 2.9 wt% or less, 2.8 wt% or less, 2.7 wt% or less, or even 2.6 wt% or less, based on the weight of the curable thermally conductive composition.

[0024] The curable thermally conductive composition of the present invention further comprises at least one silyl-hydride (SiH)-functional polysiloxane crosslinker (also "crosslinker"). The SiH-functional polysiloxane crosslinker contains at least two silyl-hydride groups (i.e., containing at least two silicon-bonded hydrogen atoms) per molecule, or even three or more silyl-hydride groups. The SiH groups can be pendant, terminal, or a combination of both pendant and terminal. The SiH-functional polysiloxane crosslinker can have the following average chemical structure (III): [ka] In the formula, R b is independently selected at each occurrence from an alkyl group having 1 to 6 carbon atoms, and phenyl. b The group may have 1 or more carbons, 2 or more carbons, 3 or more carbons, 4 or more carbons, or even 5 or more carbons, and may simultaneously have 6 or less carbons, 5 or less carbons, 4 or less carbons, 3 or less carbons, or even 2 or less carbons. b The radicals are independently selected at each occurrence from methyl and phenyl radicals.

[0025] H is a hydrogen atom, The subscripts h and h' refer to the average number of terminal hydrogen atoms at both ends, and each is independently selected at each occurrence from a value ranging from zero to 3, provided that the combination of a, h, and h' is at least 2. Desirably, h and h' are independently at each occurrence zero or more, 1 or more, or even 2 or more, and simultaneously 3 or less, 2 or less, or even 1 or less. More desirably, h and h' have the same value. Most desirably, h and h' are both zero. The subscript e represents the (HR bis the average number of a, SiO) groups. When h and h' are both zero, e ranges from 2 to 30. When h and h' are not both zero, subscript e can be zero to 30, provided that the combination of a, h, and h' is 2 or greater. Desirably, subscript e is 1 or greater, and can be 2 or greater, 3 or greater, 4 or greater, 5 or greater, 6 or greater, 7 or greater, 8 or greater, or even 9 or greater, and at the same time is typically 30 or less, and is 25 or less, 20 or less, 15 or less, 10 or less, 9 or less, 8 or less, 7 or less, 6 or less, 5 or less, 4 or less, 3 or less, or even 2 or less.

[0026] The subscript f denotes the number of (R b 2SiO) groups. In general, the subscript f is 5 or more, 10 or more, 20 or more, 25 or more, 30 or more, 40 or more, 50 or more, and can be 75 or more, 100 or more, 125 or more, 150 or more, 175 or more, or even 190 or more, and at the same time is typically 200 or less, 175 or less, 150 or less, 125 or less, 100 or less, 75 or less, 50 or less, 40 or less, 30 or less, 25 or less, or even 20 or less.

[0027] Suitable SiH functional polysiloxane crosslinkers can include, for example, trimethylsiloxy terminated poly(dimethylsiloxane / methylhydrogensiloxane), trimethylsiloxy terminated polymethylhydrogensiloxane, hydrogen terminated polydimethylsiloxane, hydrogen terminated poly(dimethylsiloxane / methylhydrogensiloxane), or mixtures thereof. The crosslinker can be a combination of two or more crosslinkers that can differ in one or more properties selected from molecular weight, structure, siloxane units, and sequence. Suitable commercially available SiH crosslinkers include those available under the designations HMS-071, HMS-501, and DMS-H11, all available from Gelest. Desirably, the crosslinker can be a combination of one or both of the polymers selected from the group consisting of: (i) trimethyl terminated dimethyl-co-hydrogen methyl polysiloxanes having a viscosity of 10-15 mPa*sec and containing 0.36 weight percent hydrogen in the silyl-hydride groups, and (ii) hydride terminated polydimethylsiloxanes having a viscosity in the range of 7-10 mPa*sec and containing 0.16 weight percent hydrogen in the silyl-hydride groups.

[0028] The concentration of the SiH functional polysiloxane crosslinker is sufficient to provide a molar ratio of silicon-bonded hydrogen atoms from the crosslinker to alkenyl groups (desirably vinyl groups) in the curable thermally conductive composition (also called "SiH / Vi ratio") that is 0.4 or more, can be 0.5 or more, 0.6 or more, 0.7 or more, 0.8 or more, or even 0.9 or more, and at the same time can be 1.5 or less, can be 1.4 or less, 1.2 or less, 1.0 or less, 0.9 or less, 0.8 or less, 0.7 or less, or even 0.6 or less. The SiH / Vi ratio determines the degree of crosslinking that occurs when the curable thermally conductive composition is cured. If the SiH / Vi ratio is too low, the composition tends not to cure sufficiently. If the SiH / Vi ratio is too high, the composition can be over-cured and become brittle, which can cause surface cracking problems.

[0029] The curable thermally conductive composition of the present invention further comprises a thermally conductive filler (C). The total concentration of the thermally conductive filler is 94% by weight or more, and can be 94.4% by weight or more, 94.5% by weight or more, 95% by weight or more, 95.4% by weight or more, or even 95.5% by weight or more, based on the weight of the curable thermally conductive composition, and at the same time, typically is 97% by weight or less, and can be 96.5% by weight or less, 96% by weight or less, 95.5% by weight or less, 95% by weight or less, or even 94.5% by weight or less.

[0030] Thermally conductive fillers (C) useful in the present invention can comprise and consist of a combination of at least three, and optionally four, different thermally conductive fillers, namely (c1), (c2), (c3), and optionally (c4), described below.

[0031] The first thermally conductive filler (c1) has a D50 particle size of 60 μm or more, and may have a D50 of 65 μm or more, 70 μm or more, 75 μm or more, 80 μm or more, 85 μm or more, or even 90 μm or more, and at the same time have a D50 particle size of 150 μm or less, and may have a D50 particle size of 140 μm or less, 130 μm or less, 120 μm or less, 110 μm or less, 100 μm or less, 95 μm or less, 90 μm or less, 85 μm or less, 80 μm or less, 75 μm or less, or even 70 μm or less. Desirably, the aluminum particles have a D50 of 70 to 95 μm, more desirably 70 to 90 μm. The aluminum particles may have any of the shapes including granular, ball-shaped, and needle-shaped, and desirably, the aluminum particles are spherical in shape. The concentration of aluminum particles (c1) is 30% or more by weight, based on the weight of the curable thermally conductive composition, and can be 31% or more by weight, 34% or more by weight, 35% or more by weight, 36% or more by weight, 38% or more by weight, 40% or more by weight, 42% or more by weight, 44% or more by weight, or even 46% or more by weight, and at the same time can be 55% or less by weight, 54% or less by weight, 53% or less by weight, 52% or less by weight, 51% or less by weight, 50% or less by weight, 48% or less by weight, 47% or less by weight, 46% or less by weight, 45% or less by weight, 42% or less by weight, 40% or less by weight, 38% or less by weight, or even 35% or less by weight. Desirably, the first thermally conductive filler is 30-52% by weight of aluminum particles having a D50 of 70-90 μm, based on the weight of the curable thermally conductive composition.

[0032] The second thermally conductive filler (c2) has a D50 particle size of 1 μm or more, and may have a D50 of 1.5 μm or more, 2 μm or more, 3 μm or more, 4 μm or more, or even 5 μm or more, and at the same time has a D50 particle size of 10 μm or less, and may have a D50 of 9 μm or less, 8 μm or less, 7 μm or less, 6 μm or less, or even 5 μm or less. The concentration of the second thermally conductive filler can be 20 wt% or more, 22 wt% or more, 25 wt% or more, 26 wt% or more, 27 wt% or more, 28 wt% or more, 29 wt% or more, or even 30 wt% or more, and at the same time 40 wt% or less, 38 wt% or less, 36 wt% or less, 35 wt% or less, 34 wt% or less, 33.5 wt% or less, 33 wt% or less, 32 wt% or less, or even 31 wt% or less, based on the weight of the curable thermally conductive composition. Preferably, the second thermally conductive filler is a combination of one or both of aluminum nitride and aluminum oxide. More preferably, the second thermally conductive filler is one or both of spherical aluminum oxide and irregular aluminum nitride. Preferably, the second thermally conductive filler is selected from 30-35 wt.% spherical aluminum oxide particles having a D50 of 2-5 μm, or 5-25 wt.% spherical aluminum oxide particles having a D50 of 2-5 μm combined with 5-20 wt.% irregular aluminum nitride particles having a D50 of 1-5 μm.

[0033] The third thermally conductive filler (c3) may have a D50 particle size of 0.1 μm or more, 0.2 or more, 0.3 or more, 0.5 or more, 0.7 or more, 0.8 or more, or even 0.9 μm or more, and at the same time have a D50 particle size of less than 1 μm, 0.8 μm or less, 0.6 μm or less, 0.4 μm or less, or even 0.2 μm or less. The concentration of the third thermally conductive filler (c3) may be 8 wt% or more, 10 wt% or more, 12 wt% or more, 14 wt% or more, 16 wt% or more, or even 18 wt% or more, and at the same time 20 wt% or less, 19 wt% or less, 18 wt% or less, 17 wt% or less, 15 wt% or less, 13 wt% or less, or even 11 wt% or less, based on the weight of the curable thermally conductive composition. The third thermally conductive filler may be selected from zinc oxide, aluminum oxide, or a mixture thereof. Desirably, the third thermally conductive filler is one or both of crushed or irregular zinc oxide and spherical aluminum oxide. More desirably, the third thermally conductive filler is selected from 12-18 wt. % irregular zinc oxide particles having a D50 of 0.1-0.5 μm, or 8-13 wt. % spherical aluminum oxide particles having a D50 of 0.2-0.8 μm.

[0034] The fourth thermally conductive filler (c4), which is other than the above aluminum particles (c1), has a D50 particle size of 20 μm or more, and may have a D50 of 25 μm or more, 30 μm or more, 35 μm or more, 40 μm or more, 45 μm or more, or even 50 μm or more, and at the same time has a D50 particle size of 80 μm or less, and may have a D50 of 70 μm or less, 60 μm or less, 55 μm or less, 50 μm or less, or even 45 μm or less. The concentration of the fourth thermally conductive filler can be greater than zero, greater than 2 wt%, greater than 4 wt%, greater than 6 wt%, greater than 8 wt%, greater than 10 wt%, greater than 12 wt%, greater than 14 wt%, greater than 16 wt%, or even greater than 18 wt%, and at the same time less than 20 wt%, less than 19 wt%, less than 17 wt%, less than 15 wt%, less than 13 wt%, or even less than 11 wt%, based on the weight of the curable thermally conductive composition. The fourth thermally conductive filler can be selected from any combination of one or more of aluminum nitride, aluminum oxide, magnesium oxide, and boron nitride. Desirably, the fourth thermally conductive filler is aluminum nitride particles. More desirably, the fourth thermally conductive filler, if present, is 10-20 wt% spherical aluminum nitride particles having a D50 in the range of 20-50 μm.

[0035] Thermally conductive fillers useful in the present invention may include fillers in addition to these four thermally conductive fillers listed above, or may include no thermally conductive fillers other than these four (i.e., the thermally conductive fillers consist of (c1), (c2), (c3), and optionally (c4)).

[0036] The particles may each independently have any shape, such as spherical, irregular, milled, platelets, etc. Desirably, each thermally conductive filler other than (c1) above is independently selected from the group consisting of aluminum particles, aluminum nitride particles, aluminum oxide particles, zinc oxide particles, and boron nitride particles.

[0037] Desirably, the thermally conductive filler useful in the present invention comprises or consists of: (c1) 30-52 wt. % aluminum particles having a D50 of 70-90 μm; (c2) 30-35 wt. % aluminum oxide particles having a D50 of 2-5 μm, or a combination of 5-25 wt. % aluminum oxide particles having a D50 of 2-5 μm and 5-20 wt. % aluminum nitride particles having a D50 of 1-5 μm; (c3) 12-18 wt. % zinc oxide particles having a D50 of 0.1-0.5 μm, or 8-13 wt. % aluminum oxide particles having a D50 of 0.2-0.8 μm, and, optionally, (c4) zero to 20 wt. % aluminum nitride particles having a D50 of 20-50 μm.

[0038] The curable thermally conductive compositions of the present invention include a combination of one or more filler treating agents (D). The filler treating agent (D) may comprise or consist of any combination of one or more trialkoxysilyl diorganopolysiloxanes, which may have the following structure: -Si(OR e ) groups, wherein R e may be independently selected for each occurrence from R in (IV) herein below. e Desirably, the trialkoxysilyl diorganopolysiloxane is a mono-trialkoxysiloxy-terminated diorganopolysiloxane. Suitable monotrialkoxysiloxy-terminated diorganopolysiloxanes include those having the average chemical structure (IV): [ka] In the formula, R c , R d , and R eis independently selected from hydrocarbyls having 1 to 10 carbon atoms, such as alkyl and aryl groups, for example, 1 or more, 2 or more, 3 or more, 4 or more, 5 or more, 6 or more, 7 or more, or even 8 or more carbon atoms, and typically having 10 or less, 8 or less, 6 or less, 4 or less, or even 2 or less carbon atoms, and the subscript g typically has a value of 20 or more, 25 or more, 30 or more, 40 or more, 50 or more, 60 or more, 70 or more, 80 or more, 90 or more, 100 or more, or even 110 or more, and typically has a value of 200 or less, and may be 150 or less, 125 or less, 120 or less, 110 or less, 100 or less, 90 or less, 80 or less, 70 or less, 60 or less, 50 or less, 40 or less, or even 30 or less. Desirably, the subscript g has a value in the range of 25 to 110. Each R c , R d , and R e may be the same or different. c , R d , and R e Suitable alkyl groups for R are exemplified by methyl, ethyl, propyl (e.g., iso-propyl and / or n-propyl), butyl (e.g., isobutyl, n-butyl, tert-butyl, and / or sec-butyl), pentyl (e.g., isopentyl, neopentyl, and / or tert-pentyl), hexyl, and branched saturated hydrocarbon groups of six carbon atoms. c , R d , and R e may each independently be an alkyl group, such as methyl, ethyl, and propyl. Desirably, each R c , R d , and R e is methyl. c , R d , and R e Suitable aryl groups for the aryl group include phenyl and dimethylphenyl. Particularly desirable monotrialkoxysiloxy-terminated diorganopolysiloxanes have the average formula (CH3)3SiO[(CH3)2SiO] 30Si(OCH3)3. Suitable mono-trialkoxysiloxy terminated dimethylpolysiloxanes can be synthesized according to the teachings of US Patent Application Publication No. 2006 / 0100336.

[0039] Filler treating agents (D) useful in the present invention may or may not contain a combination of one or more alkyltrialkoxysilanes. Suitable alkyltrialkoxysilanes include those having the following formula (V): [ka] In the formula, R f is, independently at each occurrence, an alkyl group having 1 or more, 2 or more, 3 or more, 4 or more, 5 or more, 6 or more, 7 or more, 8 or more, 9 or more, or even 10 or more carbon atoms, and simultaneously is typically an alkyl group having 20 or less, 18 or less, 16 or less, 14 or less, 12 or less, or even 10 or less carbon atoms; R g is, independently at each occurrence, alkyl having 1 or more, 2 or more, 3 or more, 4 or more, or even 5 or more carbon atoms, and at the same time generally having 6 or less, 5 or less, 4 or less, 3 or less, or even 2 or less carbon atoms. f R is, independently at each occurrence, an alkyl group having 6 to 20 carbon atoms. g is preferably methyl so as to form a methoxyl group bonded to the silicon atom. A particularly preferred alkyltrialkoxysilane is n-decyltrimethoxysilane. Suitable alkyltrialkoxysilanes include n-decyltrimethoxysilane available from The Dow Chemical Company as DOWSIL™ Z-6210 silane (DOWSIL is a trademark of The Dow Chemical Company) or from Gelest under the name SID2670.0.

[0040] Filler treating agents useful in the present invention may be present in a total concentration that is 0.1 wt% or greater, based on the weight of the curable thermally conductive composition, and can be 0.2 wt% or greater, 0.3 wt% or greater, 0.4 wt% or greater, 0.5 wt% or greater, 0.6 wt% or greater, 0.7 wt% or greater, 0.8 wt% or greater, 0.9 wt% or greater, 1.0 wt% or greater, 1.2 wt% or greater, 1.3 wt% or greater, or even 1.4 wt% or greater, and at the same time typically 2.5 wt% or less, 2.2 wt% or less, 2.0 wt% or less, 1.8 wt% or less, 1.6 wt% or less, 1.4 wt% or less, 1.3 wt% or less, or even 1.2 wt% or less. Desirably, the trialkoxysilyl diorganopolysiloxane is present at a concentration of 0.3 wt% or greater, and can be 0.4 wt% or greater, 0.5 wt% or greater, 0.6 wt% or greater, 0.7 wt% or greater, 0.8 wt% or greater, 0.9 wt% or greater, 1.0 wt% or greater, 1.1 wt% or greater, 1.2 wt% or greater, 1.3 wt% or greater, or even 1.4 wt% or greater, and simultaneously is typically present at a concentration of 2.5 wt% or less, and can be 2.2 wt% or less, 2.0 wt% or less, 1.9 wt% or less, 1.8 wt% or less, 1.7 wt% or less, 1.6 wt% or less, 1.5 wt% or less, or even 1.4 wt% or less, based on the weight of the curable thermally conductive composition. Simultaneously, or alternatively, the alkyltrialkoxysilane may be present in a concentration of zero or more, 0.01% or more, 0.05% or more, 0.1% or more, 0.2% or more, 0.3% or more, or even 0.4% or more by weight, based on the weight of the curable thermally conductive composition, and simultaneously, typically, is present in a concentration of 0.5% or less, 0.4% or less, 0.3% or less, or even 0.2% or less by weight. For example, the curable thermally conductive composition may be (CH3)3SiO[(CH3)2SiO] 30 Si(OCH3)3, or a combination thereof with n-decyltrimethoxysilane. Desirably, the curable thermally conductive composition comprises zero to 0.3 weight percent n-decyltrimethoxysilane, based on the weight of the curable thermally conductive composition, and a silane having an average chemical structure of (CH3)3SiO[(CH3)2SiO] 30 and 1.0 to 1.5 wt. % monotrimethoxysiloxy and trimethylsiloxy terminated polydimethylsiloxane having Si(OCH3)3.

[0041] The curable thermally conductive composition may or may not contain a combination of one or more platinum-based hydrosilylation reaction catalysts (E). Examples of such hydrosilylation catalysts include platinum(0)-1,3-divinyl-1,1,3,3-tetramethyldisiloxane (Karstedt's catalyst), HPtCl, di-μ-carbonyldi-π-cyclopentadienyldinickel, platinum-carbonyl complexes, platinum-divinyltetramethyldisiloxane complexes, platinum cyclovinylmethylsiloxane complexes, platinum acetylacetonate (acac), platinum black, platinum compounds such as chloroplatinic acid, chloroplatinic acid hexahydrate, reaction products of chloroplatinic acid with monohydric alcohols, platinum bis(ethylacetoacetate), platinum bis(acetylacetonate), platinum dichloride, and complexes of platinum compounds with olefins or low molecular weight organopolysiloxanes, or platinum compounds microencapsulated in a matrix or core-shell structure. The hydrosilylation catalyst may be part of a solution containing a complex of platinum with a low molecular weight organopolysiloxane, including a 1,3-diethenyl-1,1,3,3-tetramethyldisiloxane complex with platinum. These complexes may be microencapsulated in a resin matrix (typically a phenyl resin) or may be unencapsulated. Exemplary hydrosilylation catalysts are described in U.S. Pat. Nos. 3,159,601 and 3,220,972. The catalyst may be a 1,3-diethenyl-1,1,3,3-tetramethyldisiloxane complex with platinum.

[0042] Typically, the platinum-based hydrosilylation reaction catalyst (E) is present in a concentration sufficient to provide a platinum concentration of 0.01 wt.% or more, 0.03 wt.% or more, 0.04 wt.% or more, 0.05 wt.% or more, or even 0.06 wt.% or more, based on the weight of the curable thermally conductive composition, and while at the same time typically provides a platinum concentration of 0.6 wt.% or less, and can be 0.5 wt.% or less, 0.4 wt.% or less, 0.3 wt.% or less, 0.2 wt.% or less, 0.1 wt.% or less, 0.09 wt.% or less, 0.08 wt.% or less, 0.07 wt.% or less, 0.06 wt.% or less, 0.05 wt.% or less, or even 0.04 wt.% or less.

[0043] The curable thermally conductive compositions of the present invention may or may not further comprise a combination of one or more hydrosilylation reaction inhibitors (F) (also "inhibitors"), which may serve to stabilize the curable thermally conductive composition from premature curing and provide storage stability to the composition. Examples of suitable inhibitors include 2-methyl-3-butyn-2-ol; 3-methyl-1-butyn-3-ol; 3,5-dimethyl-1-hexyn-3-ol; 2-phenyl-3-butyn-2-ol; 3-phenyl-1-butyn-3-ol; 1-ethynyl-1-cyclohexanol; acetylene-based compounds such as 1,1-dimethyl-2-propynyl)oxy)trimethylsilane and methyl(tris(1,1-dimethyl-2-propynyloxy))silane; ene-yne ​​compounds such as 3-methyl-3-penten-1-yne and 3,5-dimethyl-3-hexen-1-yne; triazoles such as benzotriazole; hydrazine-based compounds; phosphine-based compounds; mercaptan-based compounds; 1,3,5,7-tetramethyl-1,3,5,7-tetravinyl cycloalkenyl siloxanes including methylvinyl cyclosiloxanes such as cyclotetrasiloxane and 1,3,5,7-tetramethyl-1,3,5,7-tetrahexenyl cyclotetrasiloxane, or any combination of two or more thereof.

[0044] The concentration of the inhibitor can be zero or more, 0.001% or more, 0.002% or more, or even 0.003% or more by weight, and at the same time typically be 0.5% or less, 0.3% or less, 0.1% or less, 0.05% or less, 0.01% or less, 0.005% or less, 0.004% or less, or even 0.003% or less by weight, based on the weight of the curable thermally conductive composition.

[0045] The curable thermally conductive composition of the present invention achieves an extrusion rate (ER) of 40 g / min or more. Herein, the extrusion rate is determined using a standard 30 cubic centimeter EFD syringe package at a pressure of 0.62 MegaPascal (MPa) and 25°C (further details are provided in the Extrusion Rate Test below). The thermally conductive composition may have an extrusion rate of 45 g / min or more, 50 g / min or more, 60 g / min or more, or even 70 g / min or more. ER is a useful property as a measure of extrudability, viscosity, dispensability, and suitability for use, for example, making the curable thermally conductive composition easily dispensable for application onto another material such as an electronic component or a heat sink. At the same time, the curable thermally conductive composition of the present invention provides a thermal conductivity of at least 10.0 W / m*K, or even 11.0 W / m*K or more, when measured using a hot disk according to ISO 22007-2 on a cured sample (further details are provided in the Thermal Conductivity Test below). Such high thermal conductivity and ease of dispensability make the curable thermally conductive composition particularly useful as a thermally conductive interface material for efficiently transferring heat between two components. Thermally conductive interface materials are typically used, particularly in electronic devices, to thermally couple heat-generating and heat-dissipating components. The curable thermally conductive composition may also have good uniformity and stability, as indicated by the absence of rough or powdery surfaces and the absence of oil separation, as determined by visual inspection.

[0046] The curable thermally conductive composition of the present invention may or may not include a combination of one or more solvents. The concentration of the solvent may be less than 0.01% by weight, less than 0.005% by weight, or even zero, based on the weight of the curable thermally conductive composition. Desirably, the curable thermally conductive composition is substantially free of solvent, i.e., it does not contain solvent, or it may contain traces of residual solvent from the delivery of the starting materials in the composition. The content of the solvent can be measured by gas chromatography (GC). If the amount of solvent is too high, voids tend to be generated during the curing of the curable thermally conductive composition, which may result in poor surface appearance or even reduced thermal conductivity. The solvent may be an organic solvent such as a saturated or unsaturated aliphatic or aromatic hydrocarbon, such as a hydrocarbon compound having 8-18 carbon atoms per molecule and at least one aliphatic unsaturation, such as benzene, toluene, xylene, hexane, heptane, octane, isoparaffin, tetradecene, etc.; a ketone, such as acetone, methyl ethyl ketone, or methyl isobutyl ketone; an acetate, such as ethyl acetate or isobutyl acetate; a glycol ether, such as propylene glycol methyl ether, dipropylene glycol methyl ether, propylene glycol n-butyl ether, diisopropyl ether, 1,4-dioxane, etc.; a cyclic or linear siloxane having an average degree of polymerization of 3-10, such as hexamethylcyclotrisiloxane, octamethylcyclotetrasiloxane, and / or decamethylcyclopentasiloxane; or a mixture thereof. The curable thermally conductive composition does not require the use of any solvent, such as those mentioned above, to achieve the desired ER (i.e., good processability) and TC properties above. The present invention also relates to a method of preparing a curable thermally conductive composition comprising combining an alkenyl-functional polyorganosiloxane, a SiH polysiloxane crosslinker, a thermally conductive filler, a filler treating agent, and optionally a hydroxylation reaction catalyst and inhibitor.

[0047] The present invention also includes a process for using the curable thermally conductive composition, comprising applying the curable thermally conductive composition between and in contact with two components, and then curing the curable composition while in place between the components. The application of the curable thermally conductive composition may involve extruding the curable thermally conductive composition. The curing may be performed by heating at 20-40°C, or at elevated temperatures above 40°C, such as 60-150°C or 80-120°C. Due to the low or absence of solvent in the curable thermally conductive composition, the process does not involve (i.e. does not include) extra steps to remove the solvent, such as stripping or evaporating the solvent. The curable thermally conductive composition allows for a process for using the composition without the aid of a solvent, while still providing a resulting composition having the desired ER and TC properties described above, and also makes it applicable to dispense the composition directly (e.g., by extrusion) onto a component of an article without the need for the addition of a solvent to the composition prior to use.

[0048] The present invention further includes an article comprising a curable thermally conductive composition and at least two components, the curable thermally conductive composition being between and in contact with the two components of the article. The curable thermally conductive composition may be in either a cured or uncured form. The article of the present invention is useful as a device that benefits from efficient thermal conduction between a component, such as a heat generating device, and at least one of a heat sink, a cold plate, a metal cover, or other heat dissipating component. EXAMPLES

[0049] Some embodiments of the present invention will now be described in the following examples, where all weight percentages are by weight of the thermally conductive composition and all particle sizes of fillers are D50 particle size unless otherwise specified. Table 1 shows materials for use in the sample thermally conductive compositions described herein below. Note: "Vi" stands for vinyl and "Me" stands for methyl. SYL-OFF is a trademark of Dow Corning Corporation. [Table 1] *The viscosity of polysiloxane was measured by ASTM D445-21 at 25°C; "TC filler" refers to thermally conductive filler.

[0050] IE1-8 and CE1-8 samples The sample formulations are shown in Tables 2 and 3, with the amount of each component reported in grams (g). The samples were prepared by mixing the components together using a SpeedMixer™ DAC 400 FVZ mixer from FlackTek Inc. (South Carolina, USA). Add Vi polymer, crosslinker, treating agent, and TC fillers C2 and C3 to the cup of the SpeedMixer. Mix at 1000 revolutions per minute (RPM) for 20 seconds, then at 1500 RPM for 20 seconds. Add half of the TC fillers C1, C4, and C5, if present, and mix at 1000 RPM for 20 seconds, then at 1500 RPM for 20 seconds. Add the remaining TC fillers and mix in the same manner. The resulting composition in the cup was scraped to ensure homogeneous mixing, then add inhibitor F-1 and catalyst E-1, and mix in the same manner to obtain the curable thermally conductive composition sample. The resulting thermally conductive composition samples were evaluated for extrusion rate, thermal conductivity, and appearance according to the following test methods.

[0051] Extrusion Speed ​​Test A Nordson EFD dispensing device is used to measure the extrusion rate ("ER") of the sample. The sample material is packaged in a 30 cubic centimeter syringe (EFD Syringe from Nordson Company) with a 2.54 millimeter (mm) orifice. The sample is dispensed at 25°C through the orifice by applying a pressure of 0.62 MPa to the syringe. The mass of sample (grams) extruded after 1 minute corresponds to the extrusion rate (grams / min). The objective of the present invention is to achieve an extrusion rate of at least 40 g / min.

[0052] Of note, some samples are reported as having an ER of 0 because they were powdered pastes that could not be extruded (thermal conductivity was not measured and is therefore reported as "NA").

[0053] Thermal Conductivity Test Thermal conductivity is determined by using a hot disk according to ISO22007-2. Thermal conductivity of the cured samples was measured by a hot disk TPS 2500 S instrument equipped with a 3.189 mm Kapton sensor (model 5465). The cured samples were prepared by curing the curable thermally conductive composition samples with dimensions of 25 mm*25 mm*8 mm at 120° C. for 60 minutes. The objective of the present invention is to achieve a thermal conductivity of at least 10.0 Watts per meter per Kelvin (W / m*K).

[0054] Appearance test Appearance is determined by visual inspection. Once all components are mixed, the resulting curable thermally conductive composition sample is visually inspected for surface appearance. If the composition shows a uniform surface, it indicates that the composition has good uniformity and stability, and therefore passes the appearance test. Otherwise, if a rough or powdery surface or oil separation is observed, the appearance test is failed.

[0055] Each sample was characterized for extrusion rate using the Extrusion Rate Test, thermal conductivity using the Thermal Conductivity Test, and appearance using the Appearance Test described herein above.

[0056] Table 2 contains the characterization results of the IE1-8 samples. As shown in Table 2, the IE1-8 samples all achieved the requirements of both an ER of at least 40 g / min and a TC of at least 10.0 W / m*K.

[0057] Table 3 contains the characterization results of the CE1-8 samples. The CE1-CE5 samples without aluminum filler with D50 in the range of 60-150 μm fail to achieve either an ER of at least 40 g / min and a thermal conductivity (TC) of at least 10 W / m*K, even when the samples contain only aluminum fillers smaller than 60 μm. Compared to the CE5 sample, the CE6 sample containing the same type of TC filler at a reduced total concentration achieved an ER of 47 g / min, but a much lower TC than 10 W / m*K. The CE7 and CE8 samples containing aluminum filler with D50 of 70 μm at concentrations of 21 wt% and 57.9 wt%, respectively, failed to achieve at least one or both of the TC and ER requirements. [Table 2] Note: In Table 2 and Table 3 below: "Filler wt %" refers to the total weight % of thermally conductive fillers relative to the total weight of all components in a sample. "Volume % Filler" refers to the total volume concentration of thermally conductive filler relative to the total weight of all components in a sample. "SiH / Vi ratio" refers to the molar ratio of SiH functionality to vinyl functionality from the crosslinker. "Al wt % (D50 > 60 μm)" refers to the weight % of aluminum particles having a D50 > 60 μm relative to the total weight of all components in a sample. "ER", "TC" and "appearance" were evaluated according to the test methods described above. [Table 3]

Claims

1. 1. A curable thermally conductive composition comprising: (A) 1.0 to 4.0 weight percent of an alkenyl-functional polyorganosiloxane having a viscosity in the range of 25 to 2000 millipascals*seconds as determined by ASTM D445-21 using a glass capillary Cannon-Fenske viscometer at 25 degrees Celsius, said alkenyl-functional polyorganosiloxane having the following average chemical structure (I): 【Chemistry 1】 In the formula, R a is, independently at each occurrence, an alkyl group having 1 to 6 carbon atoms; R' is, independently at each occurrence, an alkenyl group; subscript a > 0; subscript b > 0; subscript c is zero or 1; subscript d is zero or 1; (a + b) is 20 to 350; and (a + c + d) > 2; (B) a silyl-hydride functional polysiloxane crosslinker containing at least two silyl-hydride groups per molecule and present in a concentration providing a molar ratio of silicon-bonded hydrogen atoms to alkenyl groups in said composition of from 0.4 to 1.5; (C) 94 to 97 weight percent of a thermally conductive filler, (c1) 30% to less than 55% by weight of aluminum particles having a D50 in the range of 60 to 150 micrometers; (c2) 20 to 40 weight percent of a thermally conductive filler having a D50 in the range of 1 to 10 micrometers; (c3) 8 to 20 weight percent of a thermally conductive filler having a D50 in the range of 0.1 to less than 1 micrometer; and (c4) optionally a thermally conductive filler comprising zero to 20 weight percent of a thermally conductive filler other than (c1) having a D50 in the range of 20 to 80 micrometers; and (D) 0.1 to 2.5 weight percent of a filler treating agent comprising a trialkoxysilyl diorganopolysiloxane, and optionally an alkyltrialkoxysilane; A curable thermally conductive composition, wherein the weight percentages are based on the weight of the curable thermally conductive composition.

2. 10. The curable thermally conductive composition of claim 1, further comprising a platinum-based hydrosilylation reaction catalyst in an amount sufficient to provide a platinum concentration of 0.01 to 0.6 weight percent, based on the weight of the curable thermally conductive composition.

3. 3. The curable thermally conductive composition of claim 1 or 2, further comprising a hydrosilylation reaction inhibitor at a concentration of 0.001 to 0.3 weight percent, based on the weight of the curable thermally conductive composition.

4. The alkenyl-functional polyorganosiloxane comprises a vinyldimethylsiloxy-terminated polydimethylpolysiloxane having the average chemical structure (II): 【Chemistry 2】 4. The curable thermally conductive composition of claim 1, wherein Vi represents vinyl and the subscript b has a value of from 25 to 350.

5. The trialkoxysilyl diorganopolysiloxane is a mono-trialkoxysiloxy terminated diorganopolysiloxane having the average chemical structure (IV): 【Chemistry 3】 In the formula, R c , R d , and R e is independently selected at each occurrence from hydrocarbyl having 1 to 10 carbon atoms, and subscript g has a value from 25 to 110.

6. 6. The curable thermally conductive composition of any one of claims 1 to 5, wherein (c2) the thermally conductive filler having a D50 of 1 to 10 micrometers is selected from aluminum oxide, aluminum nitride, or mixtures thereof; (c3) the thermally conductive filler having a D50 of 0.1 to less than 1 micrometers is selected from zinc oxide, aluminum oxide, or mixtures thereof; and (c4) optionally, the thermally conductive filler having a D50 of 20 to 50 micrometers is aluminum nitride.

7. 7. The curable thermally conductive composition according to any one of claims 1 to 6, wherein the aluminum particles have a D50 of 70 to 95 micrometers.

8. 8. The curable thermally conductive composition of claim 1, wherein the thermally conductive filler comprises: (c1) 30-52 wt. % aluminum particles having a D50 of 70-90 μm; (c2) 30-35 wt. % aluminum oxide particles having a D50 of 2-5 μm, or a combination of 5-25 wt. % aluminum oxide particles having a D50 of 2-5 μm and 5-20 wt. % aluminum nitride particles having a D50 of 1-5 μm; (c3) 12-18 wt. % zinc oxide particles having a D50 of 0.1-0.5 μm, or 8-13 wt. % aluminum oxide particles having a D50 of 0.2-0.8 μm; and, optionally, (c4) zero to 20 wt. % aluminum nitride particles having a D50 of 20-50 μm.

9. 9. A process for using a curable thermally conductive composition according to any one of claims 1 to 8, comprising applying the curable thermally conductive composition between and in contact with two components and then curing the curable composition whilst in place between the components.

10. 10. The process of claim 9, wherein the applying of the curable thermally conductive composition involves extruding the curable thermally conductive composition.

11. 9. An article comprising the curable thermally conductive composition of any one of claims 1 to 8 between and in contact with two components of the article, said curable thermally conductive composition being either in a cured or uncured form.

Citation Information

Patent Citations

  • Thermally conductive composition

    WO2016190188A1

  • One-pack curable type thermally conductive silicone grease composition and electronic / electrical component

    WO2018079215A1

  • Thermally conductive resin composition, heat dissipation sheet, heat dissipation member and method for producing same

    WO2018131486A1

  • Highly thermally-conductive silicone composition

    WO2021235214A1